Have Fun in Burma : a Novel - Metro, Rosalie (NIU Southeast Asian series., 2018)
"Adela Frost wants to do something with her life. When a chance encounter and a haunting dream steer her toward distant Burma, she decides to spend the summer after high school volunteering in a Buddhist monastery. Adela finds fresh confidence as she immerses herself in her new environment, teaching English to the monks and studying meditation with the wise abbot. Then there's her secret romance with Thiha, an ex-political prisoner with a shadowy past. But when some of the monks express support for the persecution of the country's Muslim minority, Adela glimpses the turmoil that lies beneath Burma's tranquil surface. While investigating the country's complex history, she becomes determined to help stop communal violence. With Thiha's assistance, she concocts a scheme that quickly spirals out of control. Adela must decide whether to back down or double down, while protecting those she cares about from the backlash of Buddhist and Muslim extremists. Set against the backdrop of Burma's fractured transition to democracy, this coming-of-age story weaves critiques of voluntourism and humanitarian intervention into a young woman's quest for connection across cultural boundaries."--Provided by publisher.